2020
DOI: 10.15604/ejef.2020.08.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion and Poverty Alleviation Among Smallholder Farmers in Zimbabwe

Abstract: The study sought to investigate the impact of financial inclusion on poverty reduction in Zimbabwe among the smallholder farmers. It is alleged that financial inclusion can help in achieving seven of the seventeen sustainable development goals (SDGs), which include poverty eradication in all its forms everywhere, ending hunger, achieving food security, ensuring improved nutrition as well as promoting sustainable agriculture and many others. Using the simple regression method, the study discovered that financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The 4IR is founded on the utilisation of technology, digitisation of processes, and the digital transformation of business processes and other aspects of the economy. In relation to the financial services sector, digital transformation entails the provision of digital financial services [11,12]. These services are obtained and delivered through digital platforms and mobile devices.…”
Section: Industry 40 In the Financial Services Sector In Africamentioning
confidence: 99%
“…The 4IR is founded on the utilisation of technology, digitisation of processes, and the digital transformation of business processes and other aspects of the economy. In relation to the financial services sector, digital transformation entails the provision of digital financial services [11,12]. These services are obtained and delivered through digital platforms and mobile devices.…”
Section: Industry 40 In the Financial Services Sector In Africamentioning
confidence: 99%
“…In Zimbabwe, there was no information regarding the progress of SDG 1. However, Mhlanga et al (2020) posit that access to borrowing and taking out insurance, among others, may be critical to eradicating extreme poverty, a district study show that challenges remain in eradicating extreme poverty despite organizational intervention and availability of saving and lending schemes (Kabonga et al, 2021). These indicative that the country may be lagging behind in achieving SDG 1 partly because most smallholder farmers do not have access to lending schemes, citing inadequate collateral, exorbitant interest rates and liquidity problem as major bottlenecks (e.g., Dube et al, 2015;Mutambara, 2016).…”
Section: Tracking Progress Of Sdgs 1 and 2 In South Africa And Zimbabwementioning
confidence: 99%
“…It was suggested, including other things, that the government increase its efforts to satisfy the financial needs of the rural in order to promote digitalization [34]. The study revealed that digitalization had a significant influence on poverty reduction among small and marginal farmers using the basic regression method, conducting financial literacy campaigns among farmers since these characteristics are crucial in affecting farmers' involvement in financial inclusion or prohibiting them from doing so [42]. Regarding India's rising economic prominence and estimates that the Indian economy would be as big as the US economy by 2050, microfinance is an equalizer that allows all citizens to participate in and benefit from economic progress [35].…”
Section: Review Of Literature and Hypotheses Formulationmentioning
confidence: 99%